2016
DOI: 10.1016/j.jped.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal socioeconomic factors and nutritional outcomes in children under 5 years of age

Abstract: Maternal level of schooling was associated with short stature in children and maternal employment with overweight, indicating the need to take into account the socioeconomic factors when proposing programs and strategies aimed at health and nutrition improvement of children, considering inter-sectoral interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
0
6
0
8
Order By: Relevance
“…This may be attributed to the fact that young women are less experienced in likely to experience adverse nutritional outcomes than children whose mothers have secondary or higher education. This implies that the higher the level of education of women, the less the incidence of adverse nutritional outcomes among their children (Dessie et al, 2019;Gea-Horta et al, 2016;Nankinga et al, 2019). Educated women are more enlightened and exposed in terms of information relating to child health.…”
Section: Underweightmentioning
confidence: 99%
“…This may be attributed to the fact that young women are less experienced in likely to experience adverse nutritional outcomes than children whose mothers have secondary or higher education. This implies that the higher the level of education of women, the less the incidence of adverse nutritional outcomes among their children (Dessie et al, 2019;Gea-Horta et al, 2016;Nankinga et al, 2019). Educated women are more enlightened and exposed in terms of information relating to child health.…”
Section: Underweightmentioning
confidence: 99%
“…Bukan hanya itu, pendidikan ibu, pekerjaan ibu, pendapatan keluarga, jumlah anak, pola asuh dan riwayat penyakit infeksi juga mempengaruhi status gizi termasuk pertumbuhan anak balita. 7,15 Selain itu, faktor lain yang dapat mempengaruhi pertumbuhan balita adalah jenis pekerjaan ayah dan jenis pekerjaan ibu. Jenis pekerjaan yang sebagian besar mejadi buruh maka diperkirakan pendapatan keluarga rendah, sehingga akan berpengaruh terhdap pemilihan bahan makanan dan akan mempengaruhi status gizi dan pertumbuhan balita.…”
Section: Pekerjaanunclassified
“…An epidemiological study conducted in Brazil indicated that approximately 35% of school-aged children are overweight 18 . The incidence of overweight in children has been increasing in the last 30 years, characterizing a public health problem and influencing short-and long-term child health 19 . Therefore, attention must be given to obesity since, besides systemic complications, it interferes with motor development, as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%